Body Height and its Estimation Utilizing Arm Span Measurements in Female Adolescents from Southern Region in Montenegro - Rajko Milašinović; Stevo Popović; Damjan Jakšić; Ivan Vasiljević; Duško Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2016)
The purpose of this study was to examine the body height in Montenegrin female adolescents from southern region as well as the relationship between arm span as an alternative to estimating the body height, which would vary from region to region in Montenegro. Our investigation analyses 139 female adolescents from the southern region in Montenegro. The anthropometric measurements were taken according to the protocol of the ISAK. Means and standard deviations regarding the anthropometric measurements were obtained. A comparison of means of body heights and arm spans within this gender group were carried out using a t-test. The relationships between body height and arm span were determined using simple correlation coefficients and their 95% confidence interval. Then a linear regression analysis was performed to examine the extent to which the arm span can reliably predict body height. The results displayed that female Southern-Montenegrins are 168.73±6.79 cm tall and have an arm span of 167.23±7.79 cm. Compared to other studies, the results of this study have shown that this gender made Southern- Montenegrins the tall population, taller than female population across the Europe and the rest of World. On the other hand, expectably, the arm span reliably predicts body height in this gender. However, the estimation equations which have been obtained in Southern-Montenegrins are, different alike in general population, since arm span was shorter than the body heights (1.50±1.00 centimetres), much more than in general population. This study also confirms the necessity for developing separate height models for each region in Montenegro.